2011
DOI: 10.1126/scitranslmed.3002543
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent GNAS Mutations Define an Unexpected Pathway for Pancreatic Cyst Development

Abstract: More than 2% of the adult U.S. population harbors a pancreatic cyst. These often pose a difficult management problem because conventional criteria cannot always distinguish cysts with malignant potential from those that are innocuous. One of the most common cystic neoplasms of the pancreas, and a bona fide precursor to invasive adenocarcinoma, is called intraductal papillary mucinous neoplasm (IPMN). To help reveal the pathogenesis of these lesions, we purified the DNA from IPMN cyst fluids from 19 patients an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

29
653
7
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 725 publications
(691 citation statements)
references
References 59 publications
29
653
7
2
Order By: Relevance
“…38 The animals with these genetic changes develop invasive intrahepatic cholangiocarcinoma from different precursor lesions, including intraductal papillary neoplasm of the bile duct-like tumors with intestinal and pancreato-biliary epithelium. 38 Among the genes whose changes appear to be less important for the development of intraductal papillary neoplasms of the bile duct due to their infrequency are GNAS, a gene that was found to be linked to the molecular pathogenesis of pancreatic intraductal papillary mucinous neoplasm, [14][15][16] b-catenin, HER2 and EGFR. Activating mutations of GNAS, which codes for a G-protein alphasubunit, were recently discovered in a high number of pancreatic intraductal papillary mucinous neoplasms, few invasive adenocarcinomas associated with intraductal papillary mucinous neoplasm and pancreatic intraepithelial neoplasia lesions and in a small number of intraductal papillary neoplasms of the bile duct.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 The animals with these genetic changes develop invasive intrahepatic cholangiocarcinoma from different precursor lesions, including intraductal papillary neoplasm of the bile duct-like tumors with intestinal and pancreato-biliary epithelium. 38 Among the genes whose changes appear to be less important for the development of intraductal papillary neoplasms of the bile duct due to their infrequency are GNAS, a gene that was found to be linked to the molecular pathogenesis of pancreatic intraductal papillary mucinous neoplasm, [14][15][16] b-catenin, HER2 and EGFR. Activating mutations of GNAS, which codes for a G-protein alphasubunit, were recently discovered in a high number of pancreatic intraductal papillary mucinous neoplasms, few invasive adenocarcinomas associated with intraductal papillary mucinous neoplasm and pancreatic intraepithelial neoplasia lesions and in a small number of intraductal papillary neoplasms of the bile duct.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10] In addition, several studies performed on human and transgenic mice revealed a number of genetic changes in key molecular pathways during intraductal papillary mucinous neoplasm development. [11][12][13][14][15][16] In contrast to the more common pancreatic intraductal papillary mucinous neoplasms, intraductal papillary neoplasms of the bile duct have not been well characterized so far, either from the clinical or from the molecular point of view. Most studies of intraductal papillary neoplasms of the bile duct are based on small number of patients, 2,[17][18][19][20][21] and the three largest studies (55-97 patients) [22][23][24] exclusively enrolled Asiatic patients, a considerable proportion of them with hepatolithiasis or Clonorchiasis infection.…”
mentioning
confidence: 99%
“…GNAS mutations have been found in 40-60% of intraductal papillary mucinous neoplasms, and are known to be exclusive to these tumors among the various pancreatic neoplasms. [4][5][6] Komatsu et al 16 reported that GNAS mutations induced the upregulation of cyclic adenosine monophosphate and overexpression of mucin protein genes in some pancreatic duct-lineage cells; therefore, GNAS mutation appears to play a key role in the secretion of abundant mucin, the most prominent characteristic phenotype of intraductal papillary mucinous neoplasms. Interestingly, the same authors also demonstrated that the exogenous expression of mutated GNAS did not confer a proliferative advantage on pancreatic cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…In 2011, it was discovered that intraductal papillary mucinous neoplasms often harbored mutations in GNAS and RNF43. [4][5][6] Most GNAS mutations found in intraductal papillary mucinous neoplasms are either R201H or R201C, which are known to induce gain of function of the encoded protein guanosine nucleotide-binding protein alpha. 7 In contrast, RNF43 mutations are mostly frameshift or nonsense mutations that are expected to induce a lossof-function of the encoded protein ring finger protein 43.…”
mentioning
confidence: 99%
“…Recently genetic mutations in genes such as guanine nucleotide binding protein, alpha stimulating (GNAS), and mutational profiles of targeted next-generation sequencing of cancer genes, have been suggested as an adjunct to cytology and CEA to improve the diagnosis of mucinous cysts and to identify early malignancy within lesions by analyzing cyst fluid 4547 . These studies are quite promising in substantiating the feasibility of detecting DNA mutations in IPMN using cyst fluid, even when these molecules are at low concentrations, though the performance of these genetic markers needs to be further evaluated in prospective in vivo clinical studies.…”
Section: Discussionmentioning
confidence: 99%